Legitimisation of the development of contra legem law and mechanisms for its containment - Ghambaryan, Artur (Bulletin of Yerevan University C: Jurisprudence, 2024)
The purpose of this research is to ascertain whether courts are endowed with legitimacy to develop law contra legem (against the law). Primarily, the article asserts that currently democratic legitimacy is in a state of crisis: elected European political leaders are refraining from engaging in politics, ceding their positions to populists, autonomous (independent) bodies, or major non-governmental organizations. Furthermore, the notion is developed that the legitimacy of laws adopted by bodies in such a political crisis is by no means a fact, but merely a presumption. Thus, the presumption of the legitimacy of the law can be challenged judicially, where the court is empowered to implicitly establish the illegitimacy of the law in case of its contradiction to legal principles. Consequently, the court may ensure the further development of law contra legem, that is, against illegitimate law. The legitimacy of the court is derived from independence, integrity, and other legal principles, which in turn also serve as a means of legitimizing the judicial act contra legem. In support of this thesis, it should be noted that no society would want a legislative requirement in its legal system that contradicts the minimum requirements of justice and whose blatant illogicality would be evident even to a fourteen-year-old child. In contrast to more radical legal realism, in the development of law contra legem, the court does not become a "sovereign," but its decision contra legem becomes a decision of the "sovereign," since 1) the text of the law continues to retain its significance for the courts; 2) the court develops law not ex nihilo but based on legal principles and is obliged to justify their application. The article also examines mechanisms of checks and balances aimed at reducing the risks of replacing representative democracy with "juristocracy" when applying the doctrine contra legem. These mechanisms of checks and balances include institutional and substantive limits on the development of law contra legem, as well as internal restraints.